2023
DOI: 10.1038/s41598-023-31842-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro hair follicle growth model for drug testing

Abstract: In vitro models of human hair follicle-like tissue could be fundamental tools to better understand hair follicle morphogenesis and hair drug screening. During prenatal development and postnatal cyclic hair regeneration, hair follicle morphogenesis is triggered by reciprocal interactions and the organization of the epithelial and mesenchymal cell populations. Given this mechanism, we developed an approach to induce hair peg-like sprouting in organoid cultures composed of epithelial and mesenchymal cells. Human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This indicates that the growth mechanism of the IVHF is similar to that of HFs in the body. Finally, after reaching the plateau, hair growth of up to 1.5 mm in length was observed, which is a level that previous studies [58] have not achieved. Overall, these results demonstrate that the SCOC we established has trichogenic potential similar to that of existing hair epithelial cell cultivation conditions.…”
Section: Discussionmentioning
confidence: 44%
“…This indicates that the growth mechanism of the IVHF is similar to that of HFs in the body. Finally, after reaching the plateau, hair growth of up to 1.5 mm in length was observed, which is a level that previous studies [58] have not achieved. Overall, these results demonstrate that the SCOC we established has trichogenic potential similar to that of existing hair epithelial cell cultivation conditions.…”
Section: Discussionmentioning
confidence: 44%
“…We successfully developed a hair follicle organoid (hair follicloid) that could regenerate hair shafts in vitro with cells of mouse origin 13 , 14 . The application of this approach to cells of human origin showed that immature hair shaft-like structures elongated in response to minoxidil, a typical hair growth-promoting agent 15 . In our previous study, we examined potential hair growth-promoting drug candidates using human hair follicloids and identified the effects of oxytocin on hair growth 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Minoxidil, a commercially available hair growth reagent, improves DP cell function to increase the production of growth factors such as VEGF and FGF7 34 , 35 . Since OXT has a similar effect, we hypothesized that OXT might be a candidate for a hair growth reagent and investigated the hair growth ability of OXT using our in vitro hair follicle organoid models 36 .
Figure 5 Gene chip analysis and enriched signaling pathway inhibition.
…”
Section: Resultsmentioning
confidence: 99%